E-Worksheet Design of STEM Integrated Sound and Light Wave Materials to Improve Student’s Knowledge and Data Literature - Febrina Febrina Rizki; Asrizal Asrizal (Physics Learning and Education, 2023)
The industrial revolution 4.0 is a digital revolution marked by a combination of technology. Changes that occur in this era are not just about technology but are closely related to literacy skills. One of the suitable literacy to answer the challenges in this era is new literacy. Electronic student worksheet is designed by integrating science, technology, engineering and mathematics (STEM) in order to increase students' knowledge and literacy. but after doing research, several problems were found in learning, firstly using electronic worksheet has not been carried out and learning is still using printed books, both STEM integration is still relatively low with a value of 28.57, the three materials of sound and light waves have a high level of thinking. high so that students find it difficult to understand the material, and the results of the four students' knowledge tests are still relatively low with a value of 40.25. The purpose of this study was to determine the validity of the STEM integrated electronic worksheet and the practicality of the STEM integrated electronic worksheet. This research includes development research (R&D) that uses a 4-D model to the practical stage. The validation involved three experts from Physics, FMIPA UNP. The results obtained using the Aiken's V formula are that the STEM-integrated electronic worksheet with a value of 0.82 in the valid category, and the practicality value of the STEM-integrated electronic worksheet is 95.55 with a very practical category. So the electronic worksheet for sound waves and light integrated STEM is suitable for use in physics learning.